Statistical Characteristics and Security Analysis over Multi-Cascade κ-μ Shadowed Channels - Xiaohong Wang; Ming Ren; Yiwei Fang; Xinji Tian; Yanyang Zeng (Journal of Advanced Transportation)
In this paper, the statistical characteristics of the multi-cascade κ-μ shadowed fading channels are investigated and analyzed under the classic Wyner’s eavesdropping model. In particular, the general accurate expressions of the probability density function and the cumulative distribution function for amplitude and signal-to-noise ratio (SNR) are derived for the first time. Moreover, we further utilize the two performance evaluation metrics including outage probability and intercept probability to investigate the impacts of cascade number and channel parameters on reliability and security. Finally, the theoretical results are consistent with the simulations, proving the correctness of the derivation. The interesting conclusion is that when the average SNR is greater than 2 dB, the reliability of the multi-cascade model will decrease as the number of cascade increases; on the contrary, more cascading can lead to stronger anti-eavesdropping ability.